2020
DOI: 10.1093/neuonc/noaa285
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of brain metastases among patients with metastatic breast cancer: a systematic review and meta-analysis

Abstract: Background Patients with metastatic breast cancer (MBC) are living longer, but development of brain metastases often limits their survival. We conducted a systematic review and meta-analysis to determine the incidence of brain metastases in this patient population. Methods Articles published from January 2000 to January 2020 were compiled from four databases using search terms related to: breast cancer, brain metastasis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 56 publications
3
114
0
6
Order By: Relevance
“…Although such data may suggest a benefit for earlier detection of breast cancer BrM, these findings are subject to lead-time-bias. Results of ongoing prospective randomized (NCT03881605, NCT04030507) and nonrandomized (NCT03617341) clinical trials are awaited to better understand the potential utility of a screening program for patients with breast cancer BrM, Previous studies have shown that patients with metastatic TNBC and HER2+ breast cancer, which represent approximately 15% and 15-20% of breast cancer cases respectively, have the highest risk of BrM [51,52]. In contrast, patients with HR+/HER2-disease represent approximately 65% of the MBC population [53,54] and have the lowest risk of BrM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such data may suggest a benefit for earlier detection of breast cancer BrM, these findings are subject to lead-time-bias. Results of ongoing prospective randomized (NCT03881605, NCT04030507) and nonrandomized (NCT03617341) clinical trials are awaited to better understand the potential utility of a screening program for patients with breast cancer BrM, Previous studies have shown that patients with metastatic TNBC and HER2+ breast cancer, which represent approximately 15% and 15-20% of breast cancer cases respectively, have the highest risk of BrM [51,52]. In contrast, patients with HR+/HER2-disease represent approximately 65% of the MBC population [53,54] and have the lowest risk of BrM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with metastatic TNBC and HER2+ breast cancer, which represent approximately 15% and 15%–20% of breast cancer cases, respectively, have the highest risk of BrM [50, 51]. In contrast, patients with HR+/HER2− disease represent approximately 65% of the MBC population [52, 53] and have the lowest risk of BrM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed that approximately one-third of those with TNBC will eventually develop brain metastasis. 19 A systematic review by Koniali et al identified younger age, hormonal and Her-2 receptor status, higher tumor stage and size, higher histological grade, high Ki67 labeling index as independent risk factors for Breast Cancer Brain Metastasis (BCBM). 20 Symptoms are variable and can be nausea, headaches, personality changes, seizures, paralysis, and cognitive impairment.…”
Section: Incidence Of Female Breast Cancermentioning
confidence: 99%
“…It's more probably that Metastatic TNBC affect to organs such as the brain by up to 32% compared to 15% of receptor-positive tumor [23]. They are less likely to affect bones (6.4%) in contrast to their luminal counterpart (9.4%), especially on patients under 40-years-old [24].…”
Section: Research Strategymentioning
confidence: 99%